ABOUT THE PROSPECTS OF DEVELOPMENT OF CRIMINALISTIC METHODOLOGIS - Lantsedova, Yulia; Grekova, Liliya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to propose, for the initiation of a discussion, the most reasonable variant of the classification of criminalistic methods and understanding the essence of each of the basic actually criminalistic methods of research. Methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. Results: a variant of the classification of criminalistic methods and an understanding of the essence of each of the basic actually criminalistic methods of research is proposed. Discussion: based on the analysis of the main points of view, the proposed by Yu.D. Tkach is a variant of the classification of criminalistic methods of research into the basic research method, general scientific methods and the criminalistic methods with a further division of the latter from the groups of methods into an actually criminalistic methods (the basic actually criminalistic methods, the general actually criminalistic methods proper, the particular actually criminalistic methods) and the borrowed criminalistic methods. Some improvement in the positions of O.A. Kirichenko, Yu.O. Lantsedova and Yu.D. Tkach made it possible to simplify the understanding of the essence of such basic actually criminalistic methods, as methods of individual and group identification, the method of grouping, methods of classification, diagnostic and situational research and the method of establishing a common source of origin. Attention is drawn to the fact that the difference between individual and group identification is based only on the quantity and quality on the trace- perceptive object or within it of those identification signs, that allow us to conclude, that they belong only to an individual trace-forming object or only to a certain group of trace-forming objects.